Relationship between balance and aerobic capacity in adolescent athletes - Cengiz Taskın; Faruk Guven; Mine Taskın (Türk Spor ve Egzersiz Dergisi)
The aim of study was to examine relationship between balance and aerobic capacity in adolescent athletes. Total fifty athletes that is twenty five female and twenty five male participated as volunteer. Male athletes (age means; 17.12±0.83 years, height means; 172.28±7.66 cm, body weight means; 64.96±9.21 kg). Female athletes (age means; 16.80±0.82 years, height means; 162.36±6.24 cm, body weight means; 53.76±5.88 kg). Athletes completed the 20-meter shuttle run test for aerobic capacity and flamingo balance test for balance. In generally, we found a significant relationship between balance and aerobic capacity (P lt;0.05). We didn’t found a significant relationship between balance and aerobic capacity for female athletes (P gt;0.05). Also, we didn’t found a significant relationship between balance and aerobic capacity for male athletes (P gt;0.05). In conclusion, it was considered that due to gender differences in the relationship between balance and aerobic capacity. However, it was said that no differences between Athletes (female and male as separate) with the same physical characteristics.